Effects of amlodipine and perindoprilate on the structure and function of mitochondria in ventricular cardiomyocytes during ischemia‐reperfusion in the pig. (4th April 2014) - Mamou, Zahida; Chahine, Mohamed; Rhondali, Ossam; Dehina, Leila; Chevalier, Philippe; Descotes, Jacques; Bui‐Xuan, Bernard; Romestaing, Caroline; Timour, Quadiri
Abstract The aim of this study was to determine whether amlodipine and/or perindoprilate injected intravenously (iv) prior to ischemia exerted protective effects on mitochondria structural and functional alterations induced by ischemia and aggravated by reperfusion. Heart rate, the duration of monophasic action potentials (dMAP), peak of the time derivative of left ventricular pressure (LV dP/dt max), mitochondria structural and functional parameters in the left ventricle ischemic area were measured after 45‐min ischemia and 1‐min reperfusion in domestic pigs either untreated or pretreated with amlodipine, perindoprilate or amlodipine + perindoprilate. Ischemia‐reperfusion (I/R) induced tachycardia, reduced dMAP and LV dP/dt max, and causes alterations of mitochondria structural and functional parameters with decreased oxygen consumption, increased reactive oxygen species production and reduced calcium retention capacity (CRC) with opening of mitochondrial permeability transition pores. This opening is mainly due to oxidative stress and calcium overload and seems to be the pivotal event in cell death after I/R. No drug treatment changed haemodynamic and electrophysiological parameters, but amlodipine and perindoprilate, either alone or combined, prevented mitochondrial alterations but only partially. The preservation of mitochondrial structure and functions reported in our study probably plays an important role in preventing calcium overload and mPTP opening during myocardial I/R by a specially increased CRC, which can explain their cardioprotective effects.